DESCRIPTIVE STUDY OF DIETARY PATTERNS AND PHYSICAL ACTIVITIES AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS IN COMMUNITY HEALTH CENTER OF KESUNEAN, CIREBON - Hanif Haidaryafi; Muhammad Edial Sanif; Ignatius Hapsoro Wirandoko (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The prevalence of Diabetes Mellitus (DM) remains high in Indonesia. The Basic Health Research of Indonesia in 2018 revealed that 2% of 250 million population were diagnosed of DM. Unbalanced dietary patterns and lack of physical activities contributed as the risk factors of DM type 2. Particularly, this study wants to find out the description of dietary patterns and physical activities among patients in the community health center of Kesunean, Cirebon. Methodology: This descriptive study used 89 people with DM type 2 aged 45-65 years as the respondents. Consecutive sampling was used as the sampling technique, while recall questionnaire of 24-hour food consumption and food frequency for diet and Baecke questionnaire for physical activity were used as data collection techniques. Results: The results of frequency distribution analysis showed that 64 (71.9%) respondents had unbalanced diets, while 25 (28.1%) of them had balanced diets. Regarding physical activities, 51 (57.3%) respondents had low intensity of physical activities and 38 (42.7%) patients had moderate intensity of physical activities. Conclusion: Most of the respondents with DM type 2 had unbalanced diets and low intensity of physical activities. Community Health Center of Kesunean should provide communication, information and communication about the importance of balanced diets and physical activities in order to prevent the incidence of DM type 2. Keywords: Physical activity, diet, type 2 diabetes mellitus